PEMBELAJARAN MATA PELAJARAN MAKANAN INDONESIA DI ERA DIGITALISASI 5.0 - Fitri Yasih; Siti Isma Sari Lubis; Violintikha Harmawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Learners or students can no longer control the use of learning media, because indeed the demands of the world today, all people must actively take advantage of scientific facilities that are all easy to obtain in the current era of digitalization 5.0. This makes various learning sciences more and more needed from day to day. The purpose of writing this research is to find out the application of media use in learning Indonesian Food Subjects in the digitalization 5.0 era. The writing method used is a qualitative literature review research method in which the author identifies writing, data, materials with reference to Indonesian food journals and books. With the existence of learning media for the Indonesian Food subject, it is hoped that all students in the culinary field and the professional community can continue to take advantage of information opportunities that are widespread and easily accessible. In particular, continuing to preserve Indonesian culinary specialties which also compete with modern culinary delights for the popularity of local people's food in this digitalization era. The results of this study support the internationalization of the development of the 5.0 digitalization era in the implementation of making learning media for Indonesian Food subjects. There are many indicators of innovation, social environment and internationalization that can influence the development of Indonesian food learning, so that it can be accepted by the wider community and students in general.